Dental students' knowledge and attitudes towards cone beam computed tomography in Turkey - Kamburoğlu, K (The British Institute of Radiology., 2011)
OBJECTIVE: The aim of this study was to evaluate students' knowledge and attitudes regarding cone beam CT (CBCT). METHODS: A questionnaire consisting of 11 questions was given to 472 dental students (280 pre-graduate and 192 post-graduate) at two institutions located in Ankara, Turkey (Ankara University, Faculty of Dentistry, and Gazi University, Faculty of Dentistry). Differences in responses by institution, education level and sex were statistically assessed with the χ(2) test. RESULTS: Statistical results showed that only 63.3% of students had heard of CBCT. Of these, 59.9% said they had learned about CBCT in their classes, 31.0% in seminars and 20.9% from the internet; 76.8% felt that CBCT was not given adequate coverage in their courses; 69% thought that CBCT should be taught as part of their clinical education; 91% thought it essential for CBCT to be available at dental faculties; 53.5% believed that the use of CBCT would become more widespread in the near future; and 84.9% wished to use CBCT technology in their future careers. CONCLUSION: This research suggests that efforts should be made to improve students' knowledge base regarding CBCT and that the dental school curriculum should devote more curriculum time to this promising new technology.